Healthy Beauty Value Dalam Keberlangsungan Produk Wardah Di Masa Pandemi - Eva Sulastri; Rahmawaty (Lensa, 2022)
In addition to being the first and best-selling halal cosmetic in the market, Wardah also has the tagline "Green Halal Beauty" for a skin care series with a natural concept. This series was at the beginning of the pandemi and when the Pembatasan Sosial Berskala Besar (PSBB) were officially enacted, Wardah continued to exist. The existence of this series adds value or new values ​​in the sustainability of Wardah products during the pandemi. In this study, we use descriptive qualitative methods with literature review in assessing the life cycle of Wardah products and Barthes' semiotic approach to see the values ​​produced by the existence of the Nature Daily Series. Based on this approach, it was found that Wardah also made innovations so as not to get to the "saturation" stage and in order to keep Wardah known to the public or cosmetic consumers.